THE CONCEPT OF POLITICAL CULTURE AND ITS THEORETICAL FOUNDATIONS (World Bulletin of Management and Law, 2023)
The article examines the phenomenon of political culture as the most important component of the political life of society. The content and essence of the concept, the history of the formation of political culture and the level of political culture of citizens, and the stages of development are studied on an analytical basis. Also, how to form a political culture? The questions of what are the most important tasks facing the researchers-scientists engaged in this field today have been answered to a certain extent. Based on these, some aspects of political culture are revealed with a creative approach